The role of social networks in shaping entrepreneurial exit strategies - Eugene Kaciak (2020)
© 2020, Springer Science+Business Media, LLC, part of Springer Nature. Extant literature looks at entrepreneurial exit strategies (e.g., stewardship—family succession; financial harvest—sale of the firm; and voluntary cessation—voluntary liquidation) from the limited perspectives of either a small business owner’s human capital or firm/environmental characteristics. Our study adds to this research by focusing on yet another crucial capital of a small business (family or non-family) owner—his or her social capital. Specifically, we investigate the role of social networks in shaping entrepreneurial exit strategies. We draw simultaneously upon the theory of planned behavior and two theoretical models. The first model conceptualizes that certain affect-related features of the assessment process, performed by a small business owner during subjective evaluation of his or her ownership stake, are predictors of what is known as socio-emotional wealth (SEW). The second model, on the other hand, develops theoretical connections between the SEW and the choice of an exit strategy. Thus, the two models have one common element, the SEW, which we use as a connector gluing the two perspectives into one coherent structure. We use a random sample of 302 firms operating in the European Union. We show that the relevance to small business owners and the size of their social networks are both strong predictors of entrepreneurial exit strategies.